2005
DOI: 10.1136/jmg.2005.032656
|View full text |Cite
|
Sign up to set email alerts
|

Congenital heart defects and genetic variants in the methylenetetrahydroflate reductase gene

Abstract: The apparent protective effect of the MTHFR 1298C allele against CHD could have several explanations and further study is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
71
1
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(80 citation statements)
references
References 21 publications
5
71
1
3
Order By: Relevance
“…[3][4][5]10,11,23 However, previous efforts on several folate-related gene variants have yielded conflicting or negative results. [13][14][15][16][17][18]25,26 For example, in the case of the most extensively studied MTHFR c.677 CϾT variant, the data published so far do not provide strong evidence for an overall significant association with the CHD risk in either mothers or their offspring with CHD. Limited studies have been conducted on variants of the MTRR gene.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…[3][4][5]10,11,23 However, previous efforts on several folate-related gene variants have yielded conflicting or negative results. [13][14][15][16][17][18]25,26 For example, in the case of the most extensively studied MTHFR c.677 CϾT variant, the data published so far do not provide strong evidence for an overall significant association with the CHD risk in either mothers or their offspring with CHD. Limited studies have been conducted on variants of the MTRR gene.…”
Section: Discussionmentioning
confidence: 85%
“…However, studies analyzing the association between the MTHFR polymorphism and CHD have yielded controversial results. [13][14][15][16][17][18] Increased maternal homocysteine levels were also found to be associated with an increased risk of CHD in the offspring. 12,19 The remethylation of homocysteine to form methionine is catalyzed by methionine synthase (MTR).…”
Section: Clinical Perspective On P 490mentioning
confidence: 96%
“…Interesting results sprouted in the North Europe and PCR-TAQMAN subgroup; a protective role for the CA+AA and CA genotypes was observed. Several studies also report the protective role of 1298C allele, and Hobbs et al suggested three possible explanations for the phenomenon, including: (i) an unknown functional polymorphism in linkage disequilibrium with A1298C, (ii) error-free DNA synthesis with abundant purines and pyrimidines caused by the lower activity of the MTHFR enzyme, and (iii) the selective survival of the 1298A allele [49-51]. In summary, the CC genotype of the MTHFR A1298C polymorphism had an increased risk of CHD, but the protective role of 1298C allele should be interpreted with caution.…”
Section: Discussionmentioning
confidence: 99%
“…Novejše metaanalize potrjujejo pozitivno korelacijo med polimorfizmom C677T in pojavom CHD.34 S povečanim tveganjem za CHD je povezan tudi genotip 1298CC. 35 Incidenca orofacialne shize (OFC) je 1 na 700 rojstev v vseh populacijah in je druga najpogostejša prirojena napaka.36,37 V povezavi z OFC je gen MTHFR daleč najbolj raziskan. Novejša metaanaliza, ki je preučila 18 študij, je dokazala pozitivno korelacijo med materinim genotipom 677TT in pojavnostjo OFC, medtem ko korelacije med materinim in otrokovim genotipom ter tveganjem za OFC ni dokazala.37 V študiji slovenske populacije otrok z OFC smo dokazali, da se pri otrocih z genotipi, ki kodirajo manj aktivne oblike encima MTHFR, pojavnost shize poveča do 2,5-krat.…”
Section: Povezanost Polimorfizmov V Genu Za Mthfr S Pojavnostjo šTeviunclassified